Microplastic contamination and ecological risk assessment in tropical riverine surface water of Selangor River Basin, Malaysia - Mohd Zaki, Muhammad Rozaimi; Zainuddin, Azim Haziq; Saifuddin, Muhammad Firdaus Umar; Razak, Muhammad Raznisyafiq; Mohd Isa, Noorain; Ash’aari, Zulfa Hanan; Aris, Ahmad Zaharin (American Chemical Society, 2024)
Microplastics in river ecosystems have raised global concern due to their harmful impact on aquatic organisms. This study analyzed microplastic abundance and estimated the risk posed by microplastics in the Selangor River Basin, a prominent river basin in Selangor, Malaysia. Surface water was collected from 25 sampling points and divided into three regions: upstream, tributaries, and downstream. Microplastic particles were detected by stereomicroscopy and Fourier-transform infrared spectroscopy. A total of 361 particles were detected across all the samples, with an average abundance of 1.44 ± 0.62 particles/L. Although the microplastics abundance increases from upstream (1.35 ± 0.61 particles/L) to downstream (1.87 ± 0.95 particles/L), there is no significant correlation with geographical and environmental variables in the Selangor River Basin. Majority of the microplastics were 600-1000 μm (26.3%), fiber (64.3%), transparent (51.8%), and polyethylene (38.6%). The ecological risk of microplastics was determined using the risk quotient (RQ) method, suggesting a low ecological risk of microplastics (RQ = 0.06) in the Selangor River Basin. The present study provides a baseline for microplastic contamination and basis for ecological risk in river basins. The results will be useful for supporting mitigation measures and risk management of microplastics pollution in riverine ecosystems.